Victor Bendix - nøglefigur og paria i dansk musikliv - Cornelius, Jens (Rambam. Tidsskrift for jødisk kultur og forskning, 2023)
As pianist, conductor, composer, and teacher, Victor Bendix (1851-1926) was a leading figure in Danish musical life. Bendix was born into a Jewish merchant family in Copenhagen. He was trained by Niels W. Gade, the godfather of Danish music, but later studied with Franz Liszt in Weimar. In his long career, Bendix played a highly active part in the musical life in Copenhagen, and his works were often performed in Germany too. Bendix never held any official position in Copenhagen. He worked on his own, convinced that influential circles stopped him from reaching the top. The causes were partly artistic, because Bendix distanced himself from his conservative mentor Gade, but anti-Semitism probably also played a role. Furthermore, Bendix’ atheist, radical attitude was considered scandalous by many. He belonged to the radical movement, led by his famous cousins Edvard and Georg Brandes. Also, Bendix’ tumultuous love life was a public secret. In 1900, he was deeply humiliated in the press when one of his lovers, Augusta Schiøler, tried to assassinate him. Bendix was a highly self-critical artist. His main works are four symphonies, a piano concerto, a piano trio, and a piano sonata. He also wrote a large number of songs and piano pieces: all deeply considered, thorough works that display an early influence from Gade, but also from Liszt, Wagner, and other international figures. The life and works of Bendix have lately been receiving attention again, and the first Bendix biography will be published in 2021.